Molecular targeted therapy of glioblastoma. (November 2019) - Le Rhun, Emilie; Preusser, Matthias; Roth, Patrick; Reardon, David A.; van den Bent, Martin; Wen, Patrick; Reifenberger, Guido; Weller, Michael
Highlights: Most glioblastomas are not "single pathway" diseases easily amenable to targeted therapy. The core pathways altered in glioblastoma are challenging for targeted drug design. Molecular genetic profiling may identify druggable molecular alterations in subsets of glioblastomas. Abstract: Glioblastomas are intrinsic brain tumors thought to originate from neuroglial stem or progenitor cells. More than 90% of glioblastomas are isocitrate dehydrogenase (IDH)-wildtype tumors. Incidence increases with age, males are more often affected. Beyond rare instances of genetic predisposition and irradiation exposure, there are no known glioblastoma risk factors. Surgery as safely feasible followed by involved-field radiotherapy plus concomitant and maintenance temozolomide chemotherapy define the standard of care since 2005. Except for prolonged progression-free, but not overall survival afforded by the vascular endothelial growth factor antibody, bevacizumab, no pharmacological intervention has been demonstrated to alter the course of disease. Specifically, targeting cellular pathways frequently altered in glioblastoma, such as the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR), the p53 and the retinoblastoma (RB) pathways, or epidermal growth factor receptor ( EGFR ) gene amplification or mutation, have failed to improve outcome, likely because of redundant compensatory mechanisms, insufficient target coverage related in part to the blood brain barrier, or poor tolerability and safety. Yet, uncommon glioblastoma subsets may exhibit specific vulnerabilities amenable to targeted interventions, including, but not limited to: high tumor mutational burden, BRAF mutation, neurotrophic tryrosine receptor kinase ( NTRK ) or fibroblast growth factor receptor ( FGFR ) gene fusions, and MET gene amplification or fusions. There is increasing interest in targeting not only the tumor cells, but also the microenvironment, including blood vessels, the monocyte/macrophage/microglia compartment, or T cells. Improved clinical trial designs using pharmacodynamic endpoints in enriched patient populations will be required to develop better treatments for glioblastoma.